THE EFFECT OF HEDGE FUNDS ON THE TRANSFORMATION OF THE WORLD ECONOMIC RELATIONS - FEODOR ALEKSANDROVICH Smirnov (Мир новой экономики, 2018)
Today, hedge funds are some of the most effective financial players able to show high earnings despite the crisis in the global economy and international financial markets. However, their work iscontroversial: often the high yield means the specific ways in which hedge funds reach greater heights, upto the impact on the transformation of world economic relations. The article uncovers the basic directions of such influence: the use of «event-related» strategies on the example of Argentina, which default the hedge funds had commercialized; the development of regulations and launching Trans-Pacific Partnership, which inthe long term will create conditions for the expansion of hedge funds; the involvement of hedge funds in the strong price movements on the example of Brent oil price fluctuations.Noteworthy is also the question of what financial institutions ought to be referred to the hedge fund category.In the case of extension of the term the dimensions of the problem can expand progressively.